HUBUNGAN TINGKAT PENDIDIKAN ORANG TUA DENGAN KEPEDULIAN DALAM MEMOTIVASI PENDIDIKAN ANAK SEKOLAH DASAR DI KAMPUNG LUBUK SARIK KENAGARIAN KAMBANG UTARA PESISIR SELATAN - Efendi, Dedi; Kasih, Fitria; Yasmi, Fifi (Bimbingan dan Konseling, 2013)
This research is purposed to recognize relation the parent in education grade with their care in to motivation children education on Basic School atÂ Â  KampungÂ  Lubuk SarikÂ  KenegarianÂ Â  KambangÂ  UtaraÂ  PesisirÂ  Selatan. Kind of the research which to correlation descriptive. The population on this research is some the parent have had the children who is still in studying on Basic School. Getting off samprle in this research is samplingÂ  random stratified technique. Result of account have been proved much 60 person samplin. The instrument is used in this research is like a questioner. Analysis for the dataÂ  is used Chi- quadrant use to seems relation between the parent education gradeÂ  with care into education motivator their children on Basic School. Result of this research are seemed that itâs be relation on the significant grade between the parent education grade with care their parent into education motivator aÂ  children on Basic School at Kampung Lubuk Sarik where is account of X2 > table X2 in significant 0.05 degree. Result of this research seems that is the parent education grade could been affected care into education motivator a childrenÂ  on Basic School.